Rola offshoringu w rozwoju potencjału innowacyjnego gospodarki na przykładzie krajów azjatyckich i Europy Środkowo-Wschodniej - Pełka, Wanda (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper examines the phenomenon of R&D offshoring in the global economy. The most attractive location for offshoring activities are India, China and Central and Eastern Europe. The analysis of offshoring directions allows to evaluate the impact of transnational corporations on the innovative capability of those countries and identify the advantages resulting from R&D offshoring for host countries. The main finding of this article is that the R&D offshoring in developing and transforming countries has not a global character. Its role in development of country's innovative potential is still at an inceptive stage. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 424-434